0497 Head trauma in sport and neurodegenerative disease: an introduction and review of the epidemiological evidence. (21st August 2017) - Pearce, Neil; Gallo, Valentina; McElvenny, Damien
Abstract : A number of small studies and anecdotal reports have been suggested that sports involving repeated head trauma may have long-term risks of neurodegenerative disease. There are now plausible mechanisms for these effects, and a recognition that these problems do not just occur in former boxers, but in a variety of sports involving repeated concussions, and possibly also in sports in which low-level head trauma is common. These neurodegenerative effects potentially include increased risks of impaired cognitive function and dementia, Parkinson's Disease, and amyotrophic lateral sclerosis. Many would argue for taking a precautionary approach and immediately banning or restricting sports such as boxing. However, there are important public health issues in terms of how wide the net should be cast in terms of other sports, and what remedial measures could be taken. This in turn requires a major research effort involving both clinical and basic research to understand the underlying mechanisms leading from head trauma to neurodegenerative disease, and epidemiological studies to assess the long-term consequences.